Effect of the DC-Link Capacitor Size on the Wireless Inductive-Coupled Opportunity-Charging of a Drone Battery - Andrea Carloni; Federico Baronti; Roberto Di Rienzo; Roberto Roncella; Roberto Saletti (Energies, 2020)
Wireless inductive-coupled power transfer and opportunity battery charging are very appealing techniques in drone applications. Weight and size are very critical constraints in drones, so the battery and the on-board electronics must be as light and small as possible. The on-board components involved in the resonant inductive-coupled wireless power transfer usually consist of the secondary coil, the compensation capacitor, the bridge rectifier, the LC-filter and the battery. This paper suggests a sizing of the LC-filter capacitor that improves the charging power of the battery. In addition, further on-board space and size is saved by using the stray inductance of the battery as filtering inductor. LTSpice simulations and experimental tests carried out on the prototype of a wireless power transfer circuit shows the dependency of the power delivered to the battery on the filter capacitor size. Finally, it is found that the power transfer to the battery is maximized by choosing the capacitor value that sets the LC-filter resonant frequency close to the double of the excitation frequency of the wireless charging. The drawback is a large current and voltage ripple in the battery.